Rancang Bangun Sistem Si-LIONLABS Berbasis Web : Menuju Pengelolaan Admistrasi yang Efisien dan Efektif - Moh. Pebrianto; Nur Hadi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
The development of technology and information is currently proliferating, especially in the education. However, until now the UM’s Sociology Laboratory is still using the system manually. So as an effort to upgrade and efficiency, the laboratory manager developed an Online Service and Information System for the Sociology Laboratory, abbreviated as Si-LIONLABS Website-Based. The purpose of this research is to develop website to provide updated services and information via the internet to students, lecturers, and the wider community. Si-LIONLABS is expected to make it easier for students and lecturers to access Sociology Laboratory services online so that optimal and efficient services will be created. The research development model is the ADDIE development model. ADDIE stands for the five stages of the product development model: analysis, design, development, implementation, and evaluation. The result of this development research is the creation of a Sociology Laboratory management system that is ready to be used.